2013
DOI: 10.1109/tdei.2013.6508737
|View full text |Cite
|
Sign up to set email alerts
|

Charge dynamics and its energetic features in polymeric materials

Abstract: Modeling charge transport and linking charge dynamics with dissipative processes responsible for electrical ageing are a challenging objective for developing a mature approach in insulation design. Such an approach is exemplified here for polyethylenebased materials by introducing two models describing bipolar Space Charge Limited Current in transient and steady states. They rely on two classical descriptions of the distribution function of the energy levels of trap states -single trapping level or exponential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 69 publications
(100 reference statements)
0
83
0
1
Order By: Relevance
“…When a solid looses its crystallographic order, the variation of atomic potential creates localized electronic states at the band tails called Anderson localization 14 . Other factors like impurities and chemical defects also introduce low lying localized states extending into the gap [15][16][17] . The term "trap" often refers to these localized states.…”
Section: A Electronic Charge Transport In Polymer Dielectricsmentioning
confidence: 99%
“…When a solid looses its crystallographic order, the variation of atomic potential creates localized electronic states at the band tails called Anderson localization 14 . Other factors like impurities and chemical defects also introduce low lying localized states extending into the gap [15][16][17] . The term "trap" often refers to these localized states.…”
Section: A Electronic Charge Transport In Polymer Dielectricsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26]), including silicone rubber [27]. The equivalent breakdown phenomena in liquids i.e.…”
Section: Electrical Treeing Testsmentioning
confidence: 99%
“…Each of these processes can be expected to be independent and controlled by different rate equations with different parameters [20]. In [10] it has been shown that at uniform temperature, delayed extraction leads to the formation of heterocharge, whereas recombination and superposition of charge carriers of opposite polarity lead to a suppression of heterocharge accumulation.…”
Section: Single Layer Samplesmentioning
confidence: 99%
“…Delayed extraction is a natural consequence of the model but it depends upon the polarity of the electrodes in relation to the specific dielectric material. In unfilled LDPE the trap distribution can be assumed to be dominated by the large concentration of shallow traps (see [20] and references therein). Therefore if a Fermi level can be defined for these materials it will be nearly centrally placed in the band gap.…”
Section: Band Theory Model For Space Charge In Multi-layed Samplesmentioning
confidence: 99%